Microwave Synthesis of Chloroacetic Acid with Acetic Anhydride Catalyzing Chlorination of Acetic Acid - Wang, Li-Sheng; Song, Guo-Qiang; Meng, Ying; Li, Shou-Gao; Li, Fu-Xiang (Asian Journal of Chemistry, 2013)
In this paper, the chloroacetic acid has been synthesized with the acetic anhydride catalyzing chlorination of acetic acid by microwave irradiation. The volume fraction of acetic anhydride in acetic acid, reaction time, microwave power and reaction temperature have been investigated in the self-designed experimental device. The results showed that the optimum conditions were the volume fraction of acetic anhydride in acetic acid of 20 %, reaction time of 3.5 h, microwave power of 300 W, reaction temperature of 95 ºC, the yield of chloroacetic acid was 94.31 % and the selectivity was 93.01 %. Compared with ordinary heating, the selectivity and the reaction rate of using microwave irradiation were apparently improved.